Copaiba oleoresin: evaluation of the presence of polycyclic aromatic hydrocarbons (PAHs) - Wilson Gomes da Silva; Nicoletta Cortesi; Paola Fusari (Universidade de São Paulo, 2010)
The copaiba oleoresin extracted by perforating the tree-trunk found in the Amazonian forest has been used by the native indigenous communities to treat several diseases and also as fuel for lighting and for the motorboats plying the region's rivers. Currently, the oleoresin is mostly employed as a traditional remedy, mainly for the treatment of tonsillitis and as an anti-inflammatory and healing agent in oil and capsule forms, and is also used in several industry sectors. Due to its use in oral form, especially as a traditional remedy, an analysis of the presence of polycyclic aromatic hydrocarbons (PAHs) as contaminants in the oleoresin was performed. PAHs are substances formed by two or more benzoic rings and found in the atmosphere as a residue from incomplete combustion of petroleum derivatives and industrial activities. These substances are found everywhere on land and water, and as a consequence can also be found in vegetables and foodstuffs in general. The use of products contaminated with these substances can compromise human and animal life. This study was performed on oleoresin from different areas or regions in the Amazon, using the HPLC methodology with fluorescence detection. The samples analyzed revealed different concentrations of these compounds. O óleo-resina de copaíba que é extraído mediante a perfuração do tronco da árvore que se encontra em forma nativa na floresta amazônica já era empregado pelas comunidades indígenas para a cura de várias doenças e, também, como combustível em iluminação e para o funcionamento de motores de barcos que trafegavam pelos rios da região. Hoje, é largamente empregado na medicina popular, principalmente para o tratamento de amigdalite e como antiinflamatório e cicatrizante na forma de óleo e em cápsulas, sendo utilizado, também, em vários setores da indústria. Devido ao seu uso na forma oral, principalmente na medicina popular, realizou-se um trabalho para avaliar a presença de hidrocarbonetos policíclicos aromáticos (HPAs) no referido óleo-resina, como possíveis contaminantes. Os HPAs são compostos formados por dois ou mais aneis benzenicos e encontrados na atmosfera como resíduos provenientes das combustões incompletas dos derivados de petróleo e de atividades industriais. Esses compostos, preciptando-se da atmosfera, atingem terrenos, fontes de água e, consequentemente, os vegetais e gêneros alimentícios em geral. O uso de produtos contaminados com os sudetos compostos pode comprometer vidas humanas e animais. O estudo foi realizado com amostras do referido óleo-resina provenientes de diferentes áreas ou regiões da Amazônia, empregando-se a metodologia HPLC com detecção através de fluorescência.